THE EFFECT OF MUDHARABAH FINANCING PRODUCTIVITY AND INCREASING THE MEMBER'S CAPITAL BUSINESS ON THE INCOME OF MARDHOTILAH BMT MEMBERS - Dedi Suyandi (UIN Sunan Gunung Djati Bandung, 2019)
The economic sector in Indonesia is the sector with the most contribution to the creation of employment opportunities and sources of income especially in rural areas that have low incomes. The problem of this study is about how much influence the productivity of mudharabah financing and increasing member business capital on the income of Mardhotillah BMT members in Tanjungsari District, Sumedang District by using quantitative research methods, the researchers concluded that the effect was quite strong.